2020
DOI: 10.1007/s40430-020-2224-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and parametric optimization for minimizing surface roughness during WEDM of Ti6Al4V alloy using modified TLBO algorithm

Abstract: Wire-cut electrical discharge machining (WEDM) is a widely used non-contact machining process used to cut difficultto-machine materials such as titanium, nickel and inconel alloys. WEDM is famous for producing components in diverse engineering applications, including automotive, marine, space, medical sectors with the highest accuracy and consistency. In this paper, experimental investigation on surface roughness (SR) of Ti6Al4V alloy employing WEDM process is presented using Taguchi L 16 experimental plan by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 26 publications
2
22
0
1
Order By: Relevance
“…This algorithm requires only population size and number of generations for its working with minimum computational time. Several research articles could be found with the passage of time toward the advantages and acceptance among optimization researchers communities Devarasiddappa et al (2020), Abhishek et al (2017); George et al (2019), Krishnasamy and Nanjundappan (2014). Motivated by this, the present study explores the TLBO algorithm for multi-optimization and single-optimization process performance yields during WEDM of In-625.…”
Section: Proposed Optimization Routementioning
confidence: 99%
See 1 more Smart Citation
“…This algorithm requires only population size and number of generations for its working with minimum computational time. Several research articles could be found with the passage of time toward the advantages and acceptance among optimization researchers communities Devarasiddappa et al (2020), Abhishek et al (2017); George et al (2019), Krishnasamy and Nanjundappan (2014). Motivated by this, the present study explores the TLBO algorithm for multi-optimization and single-optimization process performance yields during WEDM of In-625.…”
Section: Proposed Optimization Routementioning
confidence: 99%
“…TLBO and GRA methodology is also the unique optimization tool used to find the machining process for satisfactory machining outcomes. Devarasiddappa et al (2020) apply the TLBO algorithm to optimize the RA data of WEDMed Ti6Al4V alloy. This methodology achieves the improved result of RA by 2.65%.…”
Section: Introductionmentioning
confidence: 99%
“…Literatures where MCDM techniques such as TOPSIS [18][19][20], VIKOR [21,22], MOORA [23][24][25], ARAS [26] and others [27][28][29] are used in selecting the best machining parameters. Meta-heuristic techniques such as non-dominated sorting algorithm-II [30][31][32], particle swarm optimization [33,34], teaching-learning based optimization [35], artificial bee colony algorithm [11] etc. to evaluate the optimal performance parameters by WEDM process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicated that the improvements in the MRR, Ra, and DL were 22.37%, 44.59%, and 15.07%, respectively. The reused wire technology was applied to decrease the Ra of the WEDM of Ti6Al4V alloy [10]. The author stated that the Ra was decreased by 2.65% with the aid of the new operation.…”
Section: Introductionmentioning
confidence: 99%